Borçlunun haline münasip evinin haczedilmezliği - Akkıran, Gülfem (My University, 2020)
Tezimizin konusunu Borçlunun Haline Münasip Evinin Haczedilmezliği oluşturmaktadır. Tez çalışmamız dört bölümden oluşmaktadır. Çalışmamızın birinci bölümünde haciz kavramı, haczin tanımı, hukuki niteliği, amacı, haczedilemezlik ilkesi ve bu ilkenin düzenlenme amacı üzerinde durulmuş olup ardından kısmen haczedilemeyen mal ve haklar ile tamamen haczedilemeyen mal ve haklar açıklanmıştır. İkinci bölümde çalışmamızın da esasını oluşturan hale münasip ev kavramı anlatılmış, meskeniyet şikayetinde bulunabilecek haller ile bu şikayetin ileri sürülemeyeceği durumlar uygulamada karşılaşılan sorunlarla birlikte incelenmiştir. Üçüncü bölümde aile konutunun meskeniyet şikayetine konu olması durumu değerlendirilmiş ve meskeniyet şikayetinden feragat edilebilmesi için gereken koşullar ile bu feragatin sonuçları anlatılmıştır. Son olarak dördüncü bölümde ise meskeniyet şikayetinin özellikleri, bu şikayetin icra mahkemesinde değerlendirilme süreci ile meskeniyet şikayeti sonucunda mahkeme tarafından verilen kararlara karşı başvurulacak kanun yolları konularına değinilmiştir. Tezimizde tüm bu hususlar doktrinde yer alan görüşler ile uygulamada karşılaşılan sorunlar göz önüne alınarak güncel mahkeme kararları doğrultusunda anlatılmıştır.

The subject of our thesis is the non-distrainability of home of debtor due to propiety to his/ her situation. Our dissertaion study consists of four parts. In the first part of our dissertation, the concept of distraint, the definition of the distraint, its legal characteristic, purpose, the principle of non-distrainability and the purpose of regulating this principle are explained, and subsequently the goods and rights that cannot be partially distrained and the goods and rights that cannot be completely distrained are explained. In the second part of our dissertation, the concept of home due to propiety to his/ her situations which is the basis of our thesis is explained and then the situations that can be lodged in the complaint of abode and the situations that such complaint cannot be put forward are examined together with the problems encountered in practice. In the third part, the situation of the family residence being subject to the complaint of abode is examined and the requirements for cession of complaint of abode and the results of this cession are explained. Finally, in the fourth part, the characteristics of the complaint of abode, the assessment process of this complaint in the enforcement court and the legal remedies to be applied against the decisions made by the court as a result of the complaint of abode are examined. In our dissertation, all these topics are explained in line with the current court decisions by considering the opinions in the doctrine and the problems encountered in practice.
Keywords: Abode; Aile Konutu; Cession; Civil law; Complaint; Family Residence; Feragat Distraint; Haciz; Haczedilemezlik; Hale Münasip Ev; Medeni hukuk; Meskeniyet; Non-distrainability; Şikayet; The Home Due to Propiety to His/ Her Situation